Comparison of Secondary Metabolite Content of Pteris vittata L. in Baluran National Park and Malang and Its Effect on Environment - Sulasmi, Eko Sri; Rohmawati, Uun; Amin, Achmad Makin (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2018)
Fern is cosmopolitan plants which are almost scattered in all parts of the world, one of which is found in Baluran National Park and in Malang. The potential and benefits of these ferns are quite important for agriculture and medicine because of the chemical compounds they have, especially in Pteris vitatta L. This study aimed to analyze secondary metabolites contained in P. vittata L. in Baluran National Park, Situbondo and in Malang. The samples used were leaves and rhizome P. vittata extracted using methanol 96%, followed by a qualitative test of the content of alkaloids, flavonoids, terpenoids, polyphenols, tannins, saponins, using phytochemical screening methods with several reagents. The results showed that the leaves and Rhizome P. vittata L.. in Baluran National Park, Situbondo were positively containing secondary metabolites of terpenoids, polyphenols, tannins, saponins, and alkaloids (Dragendorf and Bouchardat reagents), whereas flavonoids were not present in all samples. However, the results of P. vitatta L. phytochemical screening around Malang State University positively contained flavonoids, polyphenols, terpenoids, alkaloids (Wagner and Dragendorf reagents). The difference in results from these two places is because the secondary metabolite content in plants is affected by stressful environmental conditions such as soil texture where it is grown or is affected by the precursors of the secondary metabolites of the metabolites.